2018
DOI: 10.1021/acs.jpcc.8b11777
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Faradaic Efficiency of Oxygen Evolution on Reduced HxWO3 Photoelectrodes

Abstract: Tungsten oxide (WO 3 ) electrodes were synthesized by spin-coating an ammonium metatungstate sol. Instability in photocurrent during water oxidation applications has previously been attributed to formation of destructive peroxide intermediates. Under constant illumination, repeated cycles of poising WO 3 electrodes at 0.98 V vs Ag/AgCl in pH 1 sulfate solution followed by measuring the open-circuit potential for several hours show reversibility in the photocurrent decay. This behavior is attributed to photochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
5
19
0
Order By: Relevance
“…4 and 5) for each EIS scan and reported as a function of the applied potential as shown in Figure 2. The results clearly reveal a significant variation (about 30 %) of the capacitance as a function of the frequency when the system is considered as an ideal capacitor, as previously reported by several authors [22][23][24]. The difference in C dl value at two different frequencies when the system is considered as an ideal capacitor clearly emphasise the error made with this assumption.…”
Section: Eis and CV Response Of A Blocking Electrode (Au)supporting
confidence: 82%
“…4 and 5) for each EIS scan and reported as a function of the applied potential as shown in Figure 2. The results clearly reveal a significant variation (about 30 %) of the capacitance as a function of the frequency when the system is considered as an ideal capacitor, as previously reported by several authors [22][23][24]. The difference in C dl value at two different frequencies when the system is considered as an ideal capacitor clearly emphasise the error made with this assumption.…”
Section: Eis and CV Response Of A Blocking Electrode (Au)supporting
confidence: 82%
“…Such an occurrence is not uncommon, as seen in our previous report, among others, on the reduction of tungsten in the synthesis of WO 3 . 29 This minimal W 5+ content is also observed in the commercially available WO 3 powder with 2.6% W 5+ , calculated from the deconvoluted W 4f XPS spectra (Fig. S7 †).…”
Section: (B) Electronic Structure Before Photocatalysismentioning
confidence: 60%
“…In 1 M NaCl, both ethanol and 2-propanol oxidation by HClO generated on H x WO 3 proceeds with 90% of the charge passed contributing to an oxidized product. Previous work by our group has shown that the oxygen evolution reaction is the dominant reaction on H x WO 3 in the sulfate electrolyte, which should result in a lower yield for alcohol oxidation in the sulfate electrolyte. Indeed, in a control experiment containing 1 M Na 2 SO 4 , we observe significantly lower conversion.…”
Section: Resultsmentioning
confidence: 99%